Flagellin/TLR5 Stimulate Myeloid Progenitors to Enter Lung Tissue and to Locally Differentiate Into Macrophages - Lei, Xin; Palomero, Jara; de Rink, Iris; de Wit, Tom; van Baalen, Martijn; Xiao, Yanling; Borst, Jannie (Frontiers in Immunology, 2021)
Toll-like receptor 5 (TLR5) is the receptor of bacterial Flagellin. Reportedly, TLR5 engagement helps to combat infections, especially at mucosal sites, by evoking responses from epithelial cells and immune cells. Here we report that TLR5 is expressed on a previously defined bipotent progenitor of macrophages (MΦs) and osteoclasts (OCs) that resides in the mouse bone marrow (BM) and circulates at low frequency in the blood. In vitro, Flagellin promoted the generation of MΦs, but not OCs from this progenitor. In vivo, MΦ/OC progenitors were recruited from the blood into the lung upon intranasal inoculation of Flagellin, where they rapidly differentiated into MΦs. Recruitment of the MΦ/OC progenitors into the lung was likely promoted by the CCL2/CCR2 axis, since the progenitors expressed CCR2 and type 2 alveolar epithelial cells (AECs) produced CCL2 upon stimulation by Flagellin. Moreover, CCR2 blockade reduced migration of the MΦ/OC progenitors towards lung lavage fluid (LLF) from Flagellin-inoculated mice. Our study points to a novel role of the Flagellin/TLR5 axis in recruiting circulating MΦ/OC progenitors into infected tissue and stimulating these progenitors to locally differentiate into MΦs. The progenitor pathway to produce MΦs may act, next to monocyte recruitment, to fortify host protection against bacterial infection at mucosal sites.